Can TODness improve (expected) performances of TODs? An exploration facilitated by non-traditional data. (September 2019) - Zhou, Jiangping; Yang, Yuling; Gu, Peiqin; Yin, Ling; Zhang, Fan; Zhang, Fang; Li, Dong
Highlights: Synthesize existing indicators of TODness and related (expected) outcomes. Formulate (new) indicators of TODness and the outcomes. Identify aspects of TODness have the most impacts on the outcomes. Show differences of the impacts across days of a week. Abstract: TODness, i.e., the extent to which the existing conditions of TOD sites meet agreed-upon TOD standards often requires substantial investment and efforts. Given this, it is legitimate and understandable that decision-makers expect as many positive outcomes from TODness (or TODs) as possible. Non-traditional data (NTD) has provided more opportunities for us to develop (new) indicators for TODness and expected outcomes that we have for TODness. NTD, could, for instance, be used to formulate indicators across more spatiotemporal resolutions and samples and measure new expected outcomes, e.g., smartphone users per hour on weekdays by metro station across a city. Based on case study of Shenzhen, China, this paper introduces indicators for TODness and expected outcomes (partially) based on NTD. Through (spatial) regressions, it identifies the specific TODness (both at the site and regional levels) or station (area) characteristics that have the most impacts on different expected outcomes on weekdays and weekends. The findings and results can on the one hand revalidate the known relationships between expected outcomes in the existing literature and TODness and on the other hand reveal new relationships between the two, which can serve as extra references for TOD-related plan formulation, evaluation and decision-making.